Mezi zaslepenymi blazny - Bok, Petr (Slovakia : Slovak Television, 1999)
Documentary about the fate of Slovak Jews during the Holocaust. Also about rabbi Michael Weissmandl, spiritual leader of the "Working Group", who rescued thousands of Slovak Jews.
With voice-over in English
Keywords: Documentary films